1976
DOI: 10.1136/pgmj.52.604.61
|View full text |Cite
|
Sign up to set email alerts
|

The place of early social assessment in the management of surgical patients

Abstract: Twenty-four percent of bed-days were occupied by patients whose discharge from hospital was delayed for social or geriatric reasons in a bed-usage survey carried out on surgical patients during a three-month period of 1973. By early social assessment with the regular help of a medical social worker it was possible to reduce such delays to 16% in a similar study during the same period of 1974. The at-risk patients were the elderly admitted as an emergency and the present policy contributed partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several studies have demonstrated that early social work screening and intervention in hospitals has led to a reduction in length of stay (Bates et al, 1976;Berkman et al, 1988;Boone et al, 1981;Critelli & Black, 1993;Evans et al, 1989;Holden, 1989). This research has contributed to the development of high risk screening by social workers as an important procedure in hospitals.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that early social work screening and intervention in hospitals has led to a reduction in length of stay (Bates et al, 1976;Berkman et al, 1988;Boone et al, 1981;Critelli & Black, 1993;Evans et al, 1989;Holden, 1989). This research has contributed to the development of high risk screening by social workers as an important procedure in hospitals.…”
mentioning
confidence: 99%